Growth and Bioactive Compounds of Lettuce as Affected by Light Intensity and Photoperiod in a Plant Factory Using External Electrode Fluorescent Lamps - Cho, Ji Yoon; Yoo, Kil Sun; Kim, Jiseon; Choi, Byung Jin; Oh, Wook (Weon'ye gwahag gi'sulji, 2020)
External electrode fluorescent lamps (EEFLs) are a new, efficient light source that can be used inplant factories. We examined the effects of light intensity and photoperiod combinations on growth,total phenolic content, antioxidant capacity, and light use efficiency of lettuce (Lactuca sativa‘Cheongchima’) in a plant factory employing EEFLs. Two-week-old seedlings were grown for 3weeks at a photosynthetic photon flux density of 150 (150P) or 200 (200P) μmol∙m-2∙s-1under 12,16, 20, or 24 h photoperiods. The air temperature was maintained at 20 ± 2°C and Yamazaki nutrientsolution was supplied using a deep flow technique. Fresh shoot and root weights increased asphotoperiod was extended, becoming greatest under the 150P/24 h condition. The shoot/root ratiowas lowest at the 24 h photoperiod under 150P and 200P conditions. Leaf length decreased at longerphotoperiods, but leaf width and number was increased; therefore, leaf shape became broader underlonger photoperiods. Leaf area increased at the 150P/20 h condition but decreased at the 200P/24 hcondition. Specific leaf weight (thickness) increased significantly as photoperiod was extendedirrespective of light intensity and became greater under 200P than 150P. Total phenolic content andantioxidant capacity increased continuously with increasing photoperiods under 150P; however, inthe 200P treatment, both increased up to 20 h, then decreased under the 24 h photoperiod. Light useefficiency was generally higher under 150P, but became similar at either light intensity under the 24h period. Considering the growth rate, leaf size, antioxidant capacity, and cropping cycle, the150P/20 h condition was deemed to be the most efficient and economical for growth of ‘Cheongchima’lettuce in a plant factory system. KCI Citation Count: 10